Fruit bearing shoot characteristics of apricot and sweet cherry cultivars in Hungary - Thurzó, S.; Drén, G.; Dani, M.; Hlevnjak, B.; Hazic, V.; Szabó, Z.; Racskó, J.; Holb, I. J.; Nyéki, J. (International Journal of Horticultural Science, 2006)
: Our study was carried out on 23 apricot and 9 sweet cherry cultivars in February 2005. Fruiting laterals were classified into four groups (0-10 cm, 10-20 cm, 20-40 cm and >40 cm) and then the density and setting of flower buds were evaluated and expressed as bud/cm. The flower bud density of four types of fruit bearing shoots and the changes in the frost resistance were studied. Shoots were collected from a young orchard in Gone (apricot), Siófok (sweet cherry) and Nagykutas (sweet cherry). There were significant differences among the cultivars in the density of flower buds. The number of flower buds/cm shoot length ranged between 0.91 and 2.20 in the average of the different fruit bearing shoot types on apricot. Based on the results, the bud density of shorter shoots is generally higher on apricot, but this is not valid for all cultivars. For cvs. Magyarkajszi and Ceglédi bíborkajszi, the highest flower bud density was detected on shoots of medium length (10-40 cm). There were fivefold and almost twofold (1.85) differences in bud density among cultivars on shoots shorter than 10 cm length and longer than 40 cm length, respectively. The ratio of the bud densities of the different types of shoots also ranged between wide boundaries. For cvs. Bayoto, Toyesi and Toyiba this ratio was 2.5-3.5, while for cv. Magyarkajszi it was 1.3.In the average of fruit bearing shoots on sweet cherry, cv. Bigarreau Burlat (1.10 bud/cm) and cv. Germersdorfi 45 (0.61 bud/cm) had the largest and the lowest flower bud density, respectively. Among the fruit bearing shoots, the largest flower bud density was in the group of 0-10 cm fruiting laterals. Among cultivars, cv. Bigarreau Burlat had the largest bud density. In the groups of n- i 0 cm, 10-20 cm, 20-30 cm and 30-40 cm fruiting laterals, the lowest flower bud density was for cv. Linda, cv. Germersdorfi 45, cv. Ferrovia and cv. Sunburst, respectively. On cvs. Van and Bigarreau Burlat, large numbers of double-set flower buds were observed on the fruit bearing shoots longer than 20 cm. Fruit setting differed on the different types of fruit bearing shoots, with the lowest value measured on above 40 cm shoots. The highest fruit setting was observed on cv. Katalin, while the lowest value was measured on cv. Germersdorfi 3.